2002
DOI: 10.1016/s0304-3959(02)00233-6
|View full text |Cite
|
Sign up to set email alerts
|

Experimental incision-induced pain in human skin: effects of systemic lidocaine on flare formation and hyperalgesia

Abstract: In order to try to gain a better understanding of the mechanisms of post-operative pain, this study was designed to psychophysically determine physiological and pharmacological characteristics of experimental pain induced by a 4-mm-long incision through the skin, fascia and muscle in the volar forearm of humans. In experiment 1, the subjects (n=8) were administered lidocaine systemically (a bolus injection of 2mg/kg for a period of 5 min followed by an intravenous infusion of 2mg/kg/h for another 40 min), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
73
0
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(83 citation statements)
references
References 62 publications
6
73
0
4
Order By: Relevance
“…In an area surrounding the site of incision we found increased pain to pinprick stimuli (secondary mechanical hyperalgesia), which confirms previous reports after incision in humans 23,24 and after other types of actual or simulated tissue injuries in volunteers. 16,28 -32 Hyperalgesia secondary to mechanical stimuli is considered the perceptual correlate of central sensitization in humans.…”
Section: Somatosensory Changes Remote From the Site Of Incision (Secosupporting
confidence: 91%
See 2 more Smart Citations
“…In an area surrounding the site of incision we found increased pain to pinprick stimuli (secondary mechanical hyperalgesia), which confirms previous reports after incision in humans 23,24 and after other types of actual or simulated tissue injuries in volunteers. 16,28 -32 Hyperalgesia secondary to mechanical stimuli is considered the perceptual correlate of central sensitization in humans.…”
Section: Somatosensory Changes Remote From the Site Of Incision (Secosupporting
confidence: 91%
“…[23][24][25] As shown recently 26,27 spontaneous activity in sensitized C-and A␊-fiber nociceptive afferents induced by deep-tissue (muscle and/or fascia) injury has been suggested as a major contributor to nonevoked ongoing pain after incision in rats. However, the different role of cutaneous and muscle tissue injury to spontaneous pain after incision was not addressed here.…”
Section: Mechanisms Of Ongoing Pain After Incisionmentioning
confidence: 99%
See 1 more Smart Citation
“…The analgesic effect of systemic lidocaine is biphasic. It has a peripheral suppression effect on acute chemically induced pain [27,28], and also a central antihyperalgesic effect [29,30]. Its modes of action have been studied and it is assumed that systemic lidocaine mediates various actions, including sodium channel blockade [14], muscarinic receptor blockade [31], N-methyl-D-aspartate (NMDA) receptor blockade [32] and inhibition of polymorphonuclear leukocyte priming and activation [33].…”
Section: Discussionmentioning
confidence: 99%
“…Suggested additional mechanisms include the ability of lidocaine to inhibit flare formation and hyperalgesia secondary to experimental incision-induced pain (9). Further research has suggested that the mechanism of action may in part be associated with N-methyl-D-aspartate receptor antagonism (10).…”
Section: Discussionmentioning
confidence: 99%